1998
DOI: 10.1038/sj.mp.4000417
|View full text |Cite
|
Sign up to set email alerts
|

The short variant of the polymorphism within the promoter region of the serotonin transporter gene is a risk factor for late onset Alzheimer's disease

Abstract: We analyzed a deletion/insertion polymorphism within the promoter region of the serotonin transporter gene (5-HTTPLR) in 81 patients with late onset Alzheimer's (AD) disease (mean age 70.02 ± 8.13 years). Control groups included 81 normal subjects with comparable age (mean age 75.6 ± 10.2) and 82 younger normal subjects (mean age 37.4 ± 9.1). Statistical analysis showed a significant difference in the genotype and gene frequencies between the AD group and normal controls ( 2 = 9.021; 2 d.f. and 2 = 5.59, 1 d.f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
39
3
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 29 publications
(30 reference statements)
6
39
3
2
Order By: Relevance
“…An increased frequency of the 5-HTTLPR short variant polymorphism and LOAD was recently reported by Li et al (32) and confirmed by us in a Brazilian sample of AD patients (33). Subsequently we demonstrated that the association of the short variant in the APOE e4 allele does not increase the risk for LOAD (34).…”
Section: Introductionsupporting
confidence: 66%
“…An increased frequency of the 5-HTTLPR short variant polymorphism and LOAD was recently reported by Li et al (32) and confirmed by us in a Brazilian sample of AD patients (33). Subsequently we demonstrated that the association of the short variant in the APOE e4 allele does not increase the risk for LOAD (34).…”
Section: Introductionsupporting
confidence: 66%
“…85 This has led investigators to consider the prevalence of the 5-HTT s allele in AD patients. Studies have been inconclusive, with some observing the s/s genotype to be more prevalent in late-onset AD 86,87 and other larger studies observing no association. 88,89 However, an increasing number of investigations suggest that diminished serotonergic function may contribute to cognitive impairment in both demented and non-demented patients.…”
Section: Serotonin Transporter Polymorphism Memory and Hippocampal Vmentioning
confidence: 99%
“…95 Similarly, there is no evidence that any of the risk genes found to be associated with AD þ P in casecontrol studies (see above) also contribute to AD risk. Though some, 96,97 but not all, 98 studies have found an association of AD with short alleles of a 44 bp insertion/deletion polymorphism in the 5 0 promoter region of HTT, it was the presence of long alleles that was associated with increased AD þ P risk. 26 In Pathway C, genes contributing major risk for idiopathic psychoses such as schizophrenia would be seen to also contribute to AD þ P risk.…”
Section: Cosegregation Of Ad þ P and Idiopathic Psychosesmentioning
confidence: 99%